Synthesis, spectroscopic profiling, biological evaluation, DFT, molecular docking and mathematical studies of 3, 5-diethyl-2r, 6c-diphenylpiperidin-4-one picrate. (16th February 2023) - Bharanidharan, S.; Savithiri, S.; Rajarajan, G.; Sugumar, P.; Nelson, A.
Abstract : The title compound 3, 5-diethyl-2r, 6c-diphenylpiperidin-4-one picrate (3, 5-DEDPPP) have been synthesised and characterised by elemental analysis, FT-IR, Mass, 1D NMR ( 1 H and 13 C), UV-Vis., and Fluorescence spectral techniques. The title compound had been optimised utilising DFT method with B3LYP/6-311++G(d, p) level of theory. First order hyperpolarisability calculation was used to determine the non-linear optical behaviour of the title molecule. The calculation of the Lewis (bonding) and Non-Lewis (anti-bonding) structural types was done to explore the intra-molecular charge transfer within the molecule. The ICT and bioactivity of the molecule are significantly influenced by the decrease of the HOMO–LUMO energy gap value. The nucleophilic and electrophilic active sites of the molecule are predicted by the MEP surface analysis. Escherichia coli, Bacillus subtilis, Vibreo cholerae, as well as fungi such Candida albicans, Aspergillus niger, and Trichophyton rubrum, were tested for the 3, 5-DEDPPP bacterial activity. To establish information about the molecular interactions between protein and this novel compound theoretically, docking studies were carried out in detail. This study is further extended and confirms our synthesised molecular structure using NMR-spectroscopy by mathematical computation through the concept of graph colouring. GRAPHICAL ABSTRACT: UF0001